Pembebanan Hak Tanggungan pada Hak Guna Bangunan Atas Tanah Hak Milik - Fadhila Vidianti (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The State, as the supreme authority over land, water, and outer space, including the natural resources within, holds the highest level of power as an entity representing the entire population. This authority includes the regulation, utilization, use, and maintenance of these resources, as well as defining the legal relationships between individuals and these resources. The primary goal of this authority is to achieve the greatest welfare for the people and to promote justice, well-being, and freedom within a society based on the principles of an independent, sovereign, just, and prosperous Indonesian legal state. In the context of Indonesian agrarian law, land is considered a part of the earth's surface and is governed by Law No. 5 of 1960 on Basic Agrarian Principles (UUPA). Land rights, such as Ownership Rights and Building Use Rights (HGB), play a crucial role in land management and use, including as collateral for credit. Mortgage Rights, regulated by Law No. 4 of 1996, provide security over land and related objects, with the right holder entitled to sell the property through public auction if the debtor fails to meet their obligations. The importance of land registration and ownership rights is regulated by Government Regulation No. 24 of 1997, which ensures legal certainty for land and property owners. Creditors, including banks, play a critical role in the economy by providing credit facilities, where collateral on land and buildings is a key aspect to ensure the security of repayment and the legal validity of transactions. The classification of creditors as separatis, preferen, and konkuren facilitates the execution of mortgage rights in the event of contract breaches, thereby providing the necessary legal protection for lenders.